Effect of ROA, Growth and DER, Value Companies Study on Manufacturing Companies Listed on Indonesia Stock Exchange In 2017-2019 - Widyakto, Adhi; NSS, RR Lulus Prapti; Satya, Irma (Economics and Business Solutions Journal, 2021)
The phenomenon that is the background of this study is that during 2017 to 2019 there are still many manufacturing industry companies listed on the Indonesia Stock Exchange, having a Price Book Value (PBV) smaller than one.   Many studies produce different results about the factors that affect PBV. The question of determinant factors arises whether that affects the PBV.   Whether PBV is affected by Profitability (ROA) sales growth (Growth), And Debt Equity Ratio (DER), this research was conducted to answer the question. The theories used in this study are: signaling theory, trade-off theory. This study used purposive sampling of 75 out of 110 manufacturing companies listed on the Indonesia stock exchange in 2019.   The data used is panel data from 2017-2019. The results of this model are expected to make a new contribution to the field of financial management. The main findings of this study are, The direct effect of Growth and DER was not significant to PBV. The effect of ROA on PBV is significant.